Observer pattern network public opinion appearance-based maturity model of biological event. (2015) - Wang, Qinghu; Bai, Mingyu; Zhou, Yuxin; Lian, Jie; Pei, Zhili
Based on the existing characteristics of network public opinion appearance, results of research and analysis indicate that the process of discovering, describing and tracking hot biological events is critical for analysis of biological events network public opinion. As biological event is the centre of analysis for network public opinion, the completeness of event modelling directly determines the profound level of analysis for network public opinion. Event model as the carrier of states representing network biological public opinion contains many aspects of knowledge, such as discovering importance and novelty of an event, describing basic form of network public opinion, and determining whether or when some events become enough or less important. In order to characterise the completeness of the public opinion states, this paper presents a maturity model of event based on observer pattern network public opinion appearance, which can excellently quantify the process of public opinion analysis.